CD4-1 and CD4-2 single positive are two major CD4 lymphocyte subpopulations in ginbuna crucian carp Carassius auratus langsdorfii - Lik Ming, Lau; Misato, Kuga; Motohiko, Sano; Goshi, Kato (Elsevier Ltd., 2023)
Fish possess two divergent forms of CD4: CD4-1 resembles the mammalian CD4 whereas CD4-2 is a unique CD4 homolog. Three CD4+ cell subpopulations were identified in fish: CD4-1 single-positive (SP), CD4-2 SP, CD4-1/CD4-2 (CD4) double-positive (DP). With the aid of monoclonal antibodies (mAbs) against CD4-1 (6D1: provided by Prof. Dr. Teruyuki Nakanishi) and CD4-2 (D5) of ginbuna, tissue distribution of CD4-1 SP, CD4-2 SP, and CD4 DP lymphocyte subsets were investigated in ginbuna. Leukocytes from peripheral blood, trunk-kidney, head-kidney, spleen, and thymus of ginbuna were stained with the mAbs 6D1 (FITC-conjugated anti-rat IgG2a) and D5 (APC-conjugated anti-mouse IgM). Rat IgG2a and mouse IgM isotype were used as the negative controls against the mAbs. The antibody-stained cells were further nuclear stained with DAPI to exclude the non-viable cells. Then, a lymphocyte gate was made in the viable cells and then further analyzed by flow cytometry. Two-color immunofluorescence analysis with 6D1 and D5 by flow cytometry revealed that the percentages of CD4-1 SP and CD4-2 SP lymphocytes were comparatively higher than CD4 DP lymphocytes in all tissues examined in ginbuna. The highest percentage of CD4-2 SP lymphocytes (~40%) was found in the thymus, while the head-kidney exhibited the highest percentages of CD4-1 SP (~30%) and CD4 DP (~5%) lymphocytes. The highest and lowest proportions of total CD4+ lymphocytes were observed in the thymus (~67%) and PBL (~26%), respectively. These findings indicated that ginbuna CD4+ lymphocyte population consists of two major subpopulations (CD4-1 SP and CD4-2 SP) and a minor subset (CD4 DP).